EFFECT EARNING PER SHARE, PRICE EARNING RATIO, QUICK RETURN ON STOCK RATIO IN MANUFACTURING COMPANY IN THE BEI PERIOD 2004-2007 - NUGROHO, DANANG ADI (Accounting, 2010)
This study aims to analyze the influence of factor earnings per share, price earnings ratio, quick ratio of stock returns on manufacturing companies in BEI. Population in this study are all manufactured the financial statements that go public in ICMD (Indonesian Capital Market Directory) in 2010 to report financial years 2004, 2005, 2006 and 2007.Sampel this research used by 31 manufacturing companies located in the BEI. With the sampling criteria with purposive sampling. The method used to test the hypothesis raised is a multiple linear regression analysis, partial (T test), simultaneous (F test), test the coefficient of determination. Based on the results of data analysis and discussion of the influence of earnings per share, price earnings ratio, quick ratio of stock return, it can be put forward some conclusions as follows: 1) earnings per share significant effect on stock return, this is indicated by the regression significance value of 0.002 which less than 0.05. 2) price earnings ratio is not significant influence on stock return, this is indicated by the regression significance value of 0.432 which is greater than 0,05.3) Variable quick ratio has insignificant effect on stock return, this is indicated by the significance of the regression of 0109 greater than 0.05. 4) The results obtained by simultaneous analysis calculated F value of 5.152 and 2.60 F table is known to berate F table> F table. So that concluded there is significant influence of the EPS, PER, QR jointly to stock return and the results of the analysis or the determination coefficient R2 of 0.114. This means that 11.4% of stock return variation explained by the variation factors changes in EPS, PER, QR. The balance of 88.6% is explained by other factors which are not observed. Keyword : Earning, Stock Ratio, Manufacture, BEI